1999
DOI: 10.1111/j.1745-9125.1999.tb00509.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Criminal Victimization on a Household's Moving Decision*

Abstract: Only a small body of research addresses the impact of criminal victimization on moving (Skogan, 1990; Taub et al. 1984). Knowledge of this under‐researched relationship is important for three reasons. First, moving is costly to the victim both in monetary and psychological terms. Second, if a victimization‐mobility relationship exists, then it may partially explain why people migrate to suburban areas from cities. Third, because residential mobility reduces social control that, in turn, potentially results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
4
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 31 publications
7
131
4
5
Order By: Relevance
“…This finding was detected for both our housing volatility measure and our index of residential stability, and regardless of the racial/ethnic composition of the neighborhood. These findings are consistent with previous research showing that increasing crime rates can negatively affect the rate of homeownership (White 2001), can lead to residential outmobility (Morenoff and Sampson 1997), and that criminal victimization induces mobility (Dugan 1999). Our results support the idea that higher rates of violent crime increase residential turnover, but also indicate that instability is enduring over time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was detected for both our housing volatility measure and our index of residential stability, and regardless of the racial/ethnic composition of the neighborhood. These findings are consistent with previous research showing that increasing crime rates can negatively affect the rate of homeownership (White 2001), can lead to residential outmobility (Morenoff and Sampson 1997), and that criminal victimization induces mobility (Dugan 1999). Our results support the idea that higher rates of violent crime increase residential turnover, but also indicate that instability is enduring over time.…”
Section: Discussionsupporting
confidence: 92%
“…That is, crime increases because social control is weak, but the increasing crime further decreases social control by breaking up social networks, decreasing participation in community activities and inducing residential mobility. Indeed, there is empirical evidence that crime can induce neighborhood mobility as households relocate in response to violent crime (Morenoff and Sampson 1997), to victimization (Dugan 1999), or as a response to an increased social disorder (Skogan 1990). Liska and Bellair (1995) determined that violent crime, robbery in particular, is associated with residential out-mobility and racial change in cities between 1950 and 1990.…”
Section: The Effect Of Crime On Residential Stabilitymentioning
confidence: 99%
“…Indeed, scholars have occasionally posited this in recent years (Bursik 1986;Schuerman and Kobrin 1986;South and Messner 2000;Xie and McDowall 2008), and there is some supportive evidence for this conjecture. For example, a study using the National Crime Victimization Survey found that experiencing a crime event increased the likelihood of exiting a neighborhood (Dugan 1999). A recent study with the same data source found some evidence for a micro contextual effect, as the awareness of victimization experienced by one's nearest four neighbors also increased residential mobility (Xie and McDowall 2008).…”
Section: Differential Ability To Exit High Crime Neighborhoodsmentioning
confidence: 99%
“…A household that is unhappy with the neighborhood, but constrained in their mobility options due to limited economic resources, will not be able to leave and therefore be resigned to accepting the level of crime in the neighborhood. Indeed, studies have frequently found that households with higher levels of income are more likely to exit the neighborhood (Crowder 2001;Dugan 1999;Myers 1999;Myers 2000;South and Crowder 1998). If economic resources are important for exiting a neighborhood, and racial/ethnic minorities have fewer economic resources in general, the implication is that they will be disproportionately unlikely to leave such neighborhoods (Massey and Denton 1985).…”
Section: Differential Ability To Exit High Crime Neighborhoodsmentioning
confidence: 99%
“…Though the evidence on the Tiebout hypothesis is mixed (Dowding, John, and Biggs 1994;Rhode and Strumpf 2000), mobility decisions do seem to reflect some key area factors such as school quality (Figlio and Lucas 2000), crime rates and victimization (Cullen and Levitt 1996;Dugan 1999), and changes in neighborhood composition (Lee, Oropesa, andKanan 1994: Crowder 2000).…”
Section: Determinants Of Living In a High-poverty Neighborhoodmentioning
confidence: 99%